2016
DOI: 10.1007/s12035-016-9950-y
|View full text |Cite
|
Sign up to set email alerts
|

Protective Role of Quercetin in Cadmium-Induced Cholinergic Dysfunctions in Rat Brain by Modulating Mitochondrial Integrity and MAP Kinase Signaling

Abstract: With the increasing evidences of cadmium-induced cognitive deficits associated with brain cholinergic dysfunctions, the present study aimed to decipher molecular mechanisms involved in the neuroprotective efficacy of quercetin in rats. A decrease in the binding of cholinergic-muscarinic receptors and mRNA expression of cholinergic receptor genes (M1, M2, and M4) was observed in the frontal cortex and hippocampus on exposure of rats to cadmium (5.0 mg/kg body weight, p.o.) for 28 days compared to controls. Cadm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(39 citation statements)
references
References 125 publications
3
36
0
Order By: Relevance
“…∆Ψm is a valuable indicator of mitochondrial functional status in living cells, and the lipophilic cation JC-1, a sensitive and non-invasive specific probe, is currently the gold standard for rapidly measuring ∆Ψm (Brooks et al, 2013 ). In this study, we found that Qcn treatment effectively recovered the ∆Ψm of RGC under hypoxia, indicating that Qcn has a protective role on mitochondrial function, which has been verified in several other types of cells and tissues, such as pancreatic β-cells (Carrasco-Pozo et al, 2016 ), the frontal cortex, hippocampus (Nichols et al, 2015 ; Gupta et al, 2017 ), mouse livers (Yu et al, 2016 ) and others. Mitochondria are the major sites of ROS production under physiologic conditions, and ROS generation is associated with mitochondrial dysfunction (Tezel, 2006 ).…”
Section: Discussionsupporting
confidence: 66%
“…∆Ψm is a valuable indicator of mitochondrial functional status in living cells, and the lipophilic cation JC-1, a sensitive and non-invasive specific probe, is currently the gold standard for rapidly measuring ∆Ψm (Brooks et al, 2013 ). In this study, we found that Qcn treatment effectively recovered the ∆Ψm of RGC under hypoxia, indicating that Qcn has a protective role on mitochondrial function, which has been verified in several other types of cells and tissues, such as pancreatic β-cells (Carrasco-Pozo et al, 2016 ), the frontal cortex, hippocampus (Nichols et al, 2015 ; Gupta et al, 2017 ), mouse livers (Yu et al, 2016 ) and others. Mitochondria are the major sites of ROS production under physiologic conditions, and ROS generation is associated with mitochondrial dysfunction (Tezel, 2006 ).…”
Section: Discussionsupporting
confidence: 66%
“…In Aβ-treated neurons, EGCG increased cell viability, reduced number of apoptotic cells and decreased reactive oxygen species (ROS) generation [ 24 ]. The reduction in nAChR–mAChR receptors and expression of mRNA for the cholinergic receptor (M1, M2 and M4) was detected in the frontal cortex and hippocampus of rats exposed to cadmium, which is known to induce cognitive deficits associated with the cholinergic system [ 25 ].…”
Section: Cholinergic Signaling and Polyphenolsmentioning
confidence: 99%
“…action of quercetin is based on its antioxidative properties [ 25 ]. In clinical studies, quercetin prevented the inactivation of nAChR and mAChR receptors in AD brain tissue [ 26 ].…”
Section: Cholinergic Signaling and Polyphenolsmentioning
confidence: 99%
“…Data have also been published regarding QE having a protective effect against Cd-induced alterations in brain cholinergic signaling and neurotoxicity in rats [28] and regarding the ability of QE to reverse the Cd-related cognitive impairment effect in female mice that were exposed to Cd during their lactating period [29]. QE protects experimental animals from memory impairment and from anxiogenic behavior induced by Cd by preventing alterations in the activities of enzymes present in rats' cerebral cortex, hippocampus, and hypothalamus [30][31][32].…”
Section: Introductionmentioning
confidence: 99%